Angiotensin‐Converting Enzyme Inhibitory Activity and Antioxidant Properties of Nepeta crassifolia Boiss & Buhse and Nepeta binaludensis Jamzad. (13th June 2012) - Tundis, Rosa; Nadjafi, Farsad; Menichini, Francesco
<x xml:space="preserve">Abstract</x> This article reports phytochemical and biological studies on Nepeta binaludensis and Nepeta crassifolia. Both species were investigated for their angiotensin‐converting enzyme (ACE) inhibitory activity and antioxidant properties through three in vitro models [2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH), 2, 2'‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid) (ABTS) and ferric reducing antioxidant power (FRAP) assay]. Aerial parts were extracted with methanol and partitioned between water and subsequently n‐hexane, ethyl acetate and n‐butanol. N. binaludensis methanol extract exerted significantly higher reducing power (1.9 μM Fe(II)/g) than did the positive control butylhydroxytoluene (63.2 μM Fe(II)/g) in FRAP assay. The highest DPPH radical scavenging activity was found for N. crassifolia, with IC50 values of 9.6 and 12.1 µg/mL for ethyl acetate and n‐butanol fractions, respectively. n‐Butanol fraction of both species showed the highest ACE inhibitory activity, with IC50 values of 59.3 and 81.7 µg/mL for N. binaludensis and N. crassifolia, respectively. Phytochemical investigations resulted in the isolation of ursolic acid, oleanolic acid, apigenin, luteolin and ixoroside. Apigenin‐7‐O‐glucoside, 8‐hydroxycirsimaritin and cirsimaritin were furthermore identified in N. crassifolia ethyl acetate‐soluble fraction. Nepetanudoside B was isolated from the n‐butanol fraction of N. binaludensis. Copyright © 2012 John Wiley & Sons, Ltd.